An alternative approach for dynamic modeling in a complexly structured and heterogeneous carbonate gas reservoir: a field case study - Pratama, E. (Springer Verlag, 2017)
This paper presents an alternative approach to integrate static and dynamic data for construction of the three-dimensional (3D) dynamic reservoir model. The integrated workflow was applied to a complexly structured and heterogeneous carbonate reservoir, in Zaakher Gas Field, Southeast Asia. In this study, the number of faults which crossed along critical flow paths through fault zones were defined and modeled. Subsequently, fault zone transmissibility was calculated and modeled to be incorporated into the dynamic model. In addition, a novel methodology to determine and define the rock region model was also proposed. Construction of the dynamic model was conducted by incorporating the upscaled static geological model, fault zone transmissibility, rock region model, reservoir characteristics, and production and pressure history, as well as well completion data into the simulator. The simulation results show that the integrated workflow for 3D dynamic modeling proposed in this study has successfully improved history matching results and have a good acceptable match. © 2017, Saudi Society for Geosciences.